EVALUASI PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN (SAP) AKRUAL DALAM PENYUSUNAN LAPORAN KEUANGAN TAHUN 2014 DAN 2015 PADA PEMERINTAH DAERAH DI INDONESIA - Berbudi Sandhi Leksono; Haryanto Haryanto (Diponegoro Journal of Accounting, 2017)
Implementation of “Standar Akuntansi Pemerintahan” (SAP) accrual in the local government of Indonesia which some local government had applied for 2 years could cause some problems. This kind of thing already happened in other country who already implemented many years before. They experienced some serious problem, some of them are left alone for years without serious efforts to solve the problem. Evaluation will be execellent first step in order to know if there is a problem happening. so that government can solve the problem do in order to achieved the goal of the implementation of the new system. This study was conducted by comparing what content that supposed to be dislosed according to SAP accrual and what content that actually disclosed in the financial statementa. It also conducted a more in-depth exploration of each content that had not been appropriately disclosed.